2011
DOI: 10.1111/j.1365-2850.2010.01680.x
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the education and training of mental health staff who work with women who have been sexually abused in childhood

Abstract: Strategies to reduce sexual assault on women patients in mental health inpatient acute wards have included effective policies, a consistent approach to recording and monitoring data relating to incidences of sexual assault, increased staff levels and improvements in the ward layout. A series of workshops were devised to enable mental health staff to work with greater awareness and sensitivity to keep women patients safer on inpatient wards. What emerged in particular during the training was the ways in which s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…These recommendations were reflected in the interviews with participants in this study. In addition to education about the connection between childhood traumas, serious mental health problems, symptoms, and addictions, education about how to be with and talk with adults about the sensitive topic of CSA is required (Phillips, 2011). These findings are similar to Ross et al (2010) who advocate for further research investigating best practices on broaching the subject of sexual violence, defined as including any form of sexual activity without consent, which includes CSA.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…These recommendations were reflected in the interviews with participants in this study. In addition to education about the connection between childhood traumas, serious mental health problems, symptoms, and addictions, education about how to be with and talk with adults about the sensitive topic of CSA is required (Phillips, 2011). These findings are similar to Ross et al (2010) who advocate for further research investigating best practices on broaching the subject of sexual violence, defined as including any form of sexual activity without consent, which includes CSA.…”
Section: Discussionmentioning
confidence: 71%
“…The findings in this study about the gaps in knowledge that fueled the discomfort for practitioners are consistent with findings in other studies in which practitioners discuss reasons why they may not assess or address CSA histories in general practice (Green et al, 2011;Tudiver, McClure, Heinonen, Scurfield, & Kreklewetz, 2000). The interviews also revealed similar concerns specific to mental health practice settings as voiced by others (Phillips, 2011;Read, Hammersley, & Rudegeair, 2007). Time, private space, and an established therapeutic alliance were identified as important elements in assessing and addressing CSA histories.…”
Section: Discussionmentioning
confidence: 91%
“…). Phillips () found that mental health staff did not know how to build therapeutic relationships with women patients especially those with histories of sexual abuse.…”
Section: Resultsmentioning
confidence: 99%
“…Increased training is not without cost implications. Phillips (2011) suggests extra training on this subject may be problematic, as are staff shortages in releasing mental health professionals to receive such training. Further research is required to investigate the efficacy and acceptability of training in this area.…”
Section: Discussionmentioning
confidence: 99%